Novel methods lift the veil on chromatin's role in gene expression. (Research'eu results magazine)
Chromatin can be regarded as the control centre of a cell : It shields DNA to protect its structure and sequence, and controls its expression and replication. An ERC grant has now allowed for a better understanding of how it does so.